(untitled) (American Journal of Technology and Applied Sciences, 2025)
Globally, particular attention is being paid to ensuring the energy efficiency of large-scale equipment in the mining and metallurgical industry by optimizing its operating modes to reduce energy costs and improve production efficiency. Currently, in developed countries, "...global energy consumption in the mining and metallurgical industry accounts for approximately 3.5% of global energy annually, with crushing processes accounting for 30-40%. By 2060, energy consumption is projected to increase by 2-8 times due to declining ore quality and growing demand for metals."